Profile of the number of contamination and death of nursing professionals affected by COVID-19 at the peak of the pandemic (Research, Society and Development, 2022)
In mid-January 2020, the World Health Organization (WHO) described the emergence of a new virus, potentially more lethal in humans, and declared an international public health emergency. Based on this assumption, the present study aims to present the profile of contamination and death of nursing professionals affected by COVID-19. It was an integrative review of the literature with a quantitative-qualitative approach to the data, using to search for the descriptors in health sciences: COVID-19; nursing; epidemiology; pandemics; nursing professional. Inclusion criteria were: all article categories (originals, literature reviews, reflections and updates, among others), articles published in Portuguese, English and Spanish, between March and August 2020. The data showed a total of 41,030 nursing professionals were contaminated, of these 449 evolved to death, with a higher prevalence of contamination between ages 31-40 17,193 (41.9%), female sex 38,888 (85%), southeast region 15,763 (38.4%), federative unit of São Paulo 6,510 (15.9%) and with greater involvement in the class of nursing technicians 24,474 (59.6%). Regarding deaths, the prevalence is between the ages of 41-50 141 (31.4%), female 284 (64%), southeast region 142 (31.6%), federative unit of São Paulo 71 (15.8%) and with greater lethality in the class of nursing technicians 263 (58.6%). In view of all the above, it is possible to characterize and present the profile of contaminated nursing professionals, with the predominance of females, of reproductive age, young and living in the Southeast region.